(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the impact of laboratory classes on the level of students’ mastery of biological disciplines. The study analyzed how laboratory classes help to better understand theoretical knowledge, develop practical skills and make science more exciting. The results of the study showed that the organization of laboratory classes based on systematic and innovative methods significantly improves the mastery of biological science.